In Vitro Antibacterial and Antibiotic Resistance Modifying Effect of Bioactive Plant Extracts on Methicillin-Resistant Staphylococcus epidermidis - Romana Chovanová; Mária Mikulášová; Štefánia Vaverková (International Journal of Microbiology)
The crude extracts of plants from Asteraceae and Lamiaceae family and essential oils from Salvia officinalis and Salvia sclarea were studied for their antibacterial as well as antibiotic resistance modifying activity. Using disc diffusion and broth microdilution assays we determined higher antibacterial effect of three Salvia spp. and by evaluating the leakage of 260 nm absorbing material we detected effect of extracts and, namely, of essential oils on the disruption of cytoplasmic membrane. The evaluation of in vitro interactions between plant extracts and oxacillin described in terms of fractional inhibitory concentration (FIC) indices revealed synergistic or additive effects of plant extracts and clearly synergistic effects of essential oil from Salvia officinalis with oxacillin in methicillin-resistant Staphylococcus epidermidis.